Nonketotic hyperglycinemia: Functional assessment of missense variants in GLDC to understand phenotypes of the disease. Issue 6 (20th March 2017) - Bravo‐Alonso, Irene; Navarrete, Rosa; Arribas‐Carreira, Laura; Perona, Almudena; Abia, David; Couce, María Luz; García‐Cazorla, Angels; Morais, Ana; Domingo, Rosario; Ramos, María Antonia; Swanson, Michael A.; Van Hove, Johan L.K.; et al.
Abstract : Genetic testing has become a formidable tool in the diagnosis of NKH. However, understanding the impact of missense‐variants is a major challenge for the application of genomics into clinical practice. Herein, to address this question, we performed a comprehensive functional and structural analysis of 19 GLDC missense‐variants identified in a cohort of 26 NKH patients. We identify an important number of mutants whose loss‐of‐functionality is associated with instability and thus, are potential targets for rescue using folding therapeutic approaches. Abstract: The rapid analysis of genomic data is providing effective mutational confirmation in patients with clinical and biochemical hallmarks of a specific disease. This is the case for nonketotic hyperglycinemia (NKH), a Mendelian disorder causing seizures in neonates and early‐infants, primarily due to mutations in the GLDC gene. However, understanding the impact of missense variants identified in this gene is a major challenge for the application of genomics into clinical practice. Herein, a comprehensive functional and structural analysis of 19 GLDC missense variants identified in a cohort of 26 NKH patients was performed. Mutant cDNA constructs were expressed in COS7 cells followed by enzymatic assays and Western blot analysis of the GCS P‐protein to assess the residual activity and mutant protein stability. Structural analysis, based on molecular modeling of the 3D structure of GCS P‐protein, was also performed. We identify hypomorphic variants that produce attenuated phenotypes with improved prognosis of the disease. Structural analysis allows us to interpret the effects of mutations on protein stability and catalytic activity, providing molecular evidence for clinical outcome and disease severity. Moreover, we identify an important number of mutants whose loss‐of‐functionality is associated with instability and, thus, are potential targets for rescue using folding therapeutic approaches.